IMPLEMENTASI MASTERY LEARNING UNTUK PENCAPAIAN STANDAR KOMPETENSI SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 2 BOGOR: Implementation Of Mastery Learning For The Achievement Of Students ' Competency Standards In Islamic Education Learning At State High School 2 Bogor - Mukhtar Mukhtar (LP2M UIN KH.Achmad Siddiq Jember, 2020)
This study aims to describe the implementation of mastery learning (complete learning) in Islamic Religious Education learning (both planning, implementation, evaluation, learning outcomes, and follow-up) in SMA Negeri 2 Bogor; also to provide a clear explanation of the implications of mastery learning on students' achievement of Competency Standards (SK) in Islamic Education learning. This research is qualitative field research. The approach used is descriptive qualitative, and data collection uses the method of observation, interviews, documentation, and triangulation. The data analysis used was descriptive-analytical and interpretive. The results show that SMA Negeri 2 Bogor has implemented the mastery learning strategy to achieve SK in learning (PAI), especially - more intensively - since the implementation of the CBC in 2004 and KTSP in 2006, but the performance has not been maximal. And needs further improvement. Implementatively, the mastery learning strategy pays close attention to individual differences, marked by the existence of follow-up programs in the form of remedial, enrichment, and acceleration programs, which of course, become necessary. So that students achieve competency ultimately. The implication is that the achievement of SK depends on the accomplishment of Basic Competence (KD), and the achievement of KD is very dependent on the achievement of indicators and vice versa. The completeness is based on the Minimum Completeness Criteria (KKM) that have been determined in Islamic Education learning so that students have competence and performance that can be measured (measurable) and can be observed (observable) as an indicator of successful learning completely.